Kondisi Penghidupan Rumahtangga Petani Di Desa Sampir Kecamatan Waringinkurung Kabupaten Serang - Mariyam, Mariyam; Hayat, Nurul (Peneliti.net, 2024)
This research seeks to provide a picture of the livelihood conditions of farmer households or farming communities in Sampir Village. The problem that is of concern in this research is how the community or farming families implements adaptation patterns for their families by implementing various livelihood strategies, to in fulfill their daily living needs. This research uses a qualitative approach with descriptive methods. With data collection techniques through observation, interviews, and dokumentation. While the processing research data is by reducing data, presenting data, and drawing conclusions. The results of this research show that the community or farming households in Sampir village, always fulfill their basic daily needs for everyday apart from agricultural products, they also always carry out various livelihood strategies. This research uses the subsistence ethnics theory explained by James C Scott regarding survival mechanisms among farmers. The comunity or farming families in Sampir Village prioritiez fulfilling basic needs rather than meeting other needs